Analisis Manajemen Program Madrasah Riset dalam Pengembangan Prestasi Siswa - Henny Nur Laili; Muhammad Thoyib (Edumanagerial, 2023)
Competition in the field of education is increasingly competitive and innovation is needed to win this competition. However, the lack of optimal management of human resources in educational institutions and the literacy crisis in young people have led to low levels of education in Indonesia. With these problems, research-based madrasah development is one of the innovations that can be done. This research aims to find out and analyze the planning, implementation and evaluation of the research madrasah program in developing student achievement. This research uses a qualitative approach with a case study method, with research data collection techniques in the form of interviews, observations, and documentation. The results showed that the planning of the research-based madrasah program was carried out by creating a special research team, involving all madrasah residents, and setting goals to be achieved. The implementation of the program is carried out by providing two special subjects in the research superior class, the implementation of the learning process is carried out for 1 hour, there are research support activities, the role of educators who are competent in the field of research and the extracurricular activities of youth scientific work. Program evaluation in the research superior class is carried out twice in the first and second semesters by a special research team and assisted by research class teachers and research homeroom teachers.